The evolution of our understanding of coronal mass ejections - Howard, Russell A.; Vourlidas, Angelos; Stenborg, Guillermo (Frontiers in Astronomy and Space Sciences, 2023)
The unexpected observation of a sudden expulsion of mass through the solar corona in 1971 opened up a new field of interest in solar and stellar physics. The discovery came from a white-light coronagraph, which creates an artificial eclipse of the Sun, enabling the viewing of the faint glow from the corona. This observation was followed by many more observations and new missions. In the five decades since that discovery, there have been five generations of coronagraphs, each with improved performance, enabling continued understanding of the phenomena, which became known as Coronal Mass Ejection (CME) events. The conceptualization of the CME structure evolved from the elementary 2-dimensional loop to basically two fundamental types: a 3-dimensional magnetic flux rope and a non-magnetic eruption from pseudo-streamers. The former persists to 1 AU and beyond, whereas the latter dissipates by 15 R⊙. Historically, most of the studies have been devoted to understanding the CME large-scale structure and its associations, but this is changing. With the advent of the fourth and fifth coronagraph generations, more attention is being devoted to the their internal structure and initiation mechanisms. In this review, we describe the evolution of CME observations and their associations with other solar and heliospheric phenomena, with one of the more important correlations being its recognition as a driver of space-weather. We conclude with a brief overview of open questions and present some ideas for future observations.